Morbidity burden in survivors of multiple myeloma who underwent autologous transplantation: A Bone Marrow Transplantation Survivor Study. Issue 14 (15th May 2020) - Arora, Mukta; Chen, Yanjun; Hageman, Lindsey; Wu, Jessica; Landier, Wendy; Francisco, Liton; Kung, Michelle; Ness, Emily; Bosworth, Alysia; Pamukcuoglu, Merve; Weisdorf, Daniel J.; Forman, Stephen J.; et al.
Abstract : Background: Autologous blood or bone marrow transplantation (aBMT) is considered the standard of care for patients with multiple myeloma (MM). Significantly improved survival necessitates an understanding of the morbidity burden borne by the growing survivor population. Methods: The authors evaluated severe and/or life‐threatening chronic health conditions (CHCs) and subsequent neoplasms (SNs) in patients with MM who were treated with aBMT using the Bone Marrow Transplant Survivor Study. A total of 630 study participants had undergone aBMT for MM at 1 of 3 BMT centers, had survived ≥2 years after aBMT, and were aged ≥18 years at the time of survey completion. Survivors of aBMT identified 289 nearest‐age siblings to constitute an unaffected comparison group. Scoring of CHCs was based on version 5 of the National Cancer Institute Common Terminology Criteria for Adverse Events to determine severity (with grade 3 indicating serious and grade 4 indicating life‐threatening). Results: The 10‐year cumulative incidence of any grade 3 to 4 CHC among survivors of aBMT was 57.6 ± 3.2%. Survivors of MM were found to be at 40% higher odds of developing grade 3 to 4 CHCs when compared with siblings (95% confidence interval [95% CI], 1.0‐1.9). Among SNs, 96% were solid tumors, yielding a 10‐year cumulative incidence of 13.6% ± 2.5%. Pre‐aBMT exposure to cyclophosphamide (hazard ratio [HR], 3.5; 95% CI, 1.5‐8.1) and immunomodulatory drugs (HR, 3.9; 95% CI, 1.5‐10.1) were associated with an increased risk of solid tumors. Melanoma (10‐year cumulative incidence: 3.3% ± 1.2%) and squamous cell carcinoma (10‐year cumulative incidence: 5.1% ± 1.8%), were the most common SNs. Pre‐aBMT exposure to cyclophosphamide (HR, 6.02; 95% CI, 1.4‐26.1) and immunomodulatory drugs (HR, 7.9; 95% CI, 0.9‐68.5) was associated with an increased risk of melanoma. Conclusions: The 10‐year cumulative incidence of severe and/or life‐threatening CHCs was found to approach 60% in long‐term survivors of MM, with solid SNs constituting a large morbidity burden. The current study has provided evidence supporting the close monitoring of survivors to manage morbidity. Abstract : The cumulative incidence of grade 3 to 4 toxicities in survivors of multiple myeloma who are treated with autologous transplantation is found to approach 60% at 10 years. The cumulative incidence of subsequent neoplasms in these individuals is 13.9% ± 2.5%.